The “Right” to a Disinterested Prosecutor of Criminal Contempt: Unpacking Public and Private Interests - Joan Meier (Washington University Law Quarterly, 1992)
In this Article I argue that, contrary to Justice Blackmun's concurring opinion and the opinions of several state courts, courts should not expand Young to establish a new due process right for criminal contemnors that would bind state courts.
Keywords: Contempt of court; Prosecutors; Criminal procedure – United States